Acute pancreatitis after coronary artery bypass surgery treated by plasmapheresis - Denli Yalvaç, Emine Şeyma; Aldağ, Mustafa; Kocaaslan, Cemal; Şenateş, Ebubekir; Aydın, Ebuzer (Turkish Journal of Gastroenterology, 2018)
Abstract Acute pancreatitis (AP) is a common disorder and an important cause of morbidity and mortality. There are different causes of AP, including gallstones and excessive alcohol consumption. AP after coronary artery bypass grafting (CABG) surgery is seen less frequently but it is associated with a high mortality rate due to its atypical and misleading symptoms. Supportive treatment, pain management, and treatment of complications are used in the treatment of AP. The treatment of hypertriglyceridemia-induced pancreatitis is plasmapheresis, which is an extracorporeal separation of blood components to assist in the removal of inflammatory mediators. Here we present the case of a 60-year-old male patient who developed severe AP (Ranson Score: 6) without hypertriglyceridemia after CABG. The patient received supportive treatment, but the response to conventional therapy was not predictable. Thus, plasmapheresis was started, and the patient was treated with plasmapheresis successfully. The use of plasmapheresis in patients with this condition is a new treatment modality as far as we know. This case illustrates the efficient and safe use of the plasmapheresis treatment modality in a patient with AP without hypertriglyceridemia. Cite this article as: Denli Yalvaç EŞ, Aldağ M, Kocaaslan C, Şenateş E, Aydın E. Acute pancreatitis after coronary artery bypass surgery treated by plasmapheresis. Turk J Gastroenterol 2018; 29: 101-3.